PRIVATE SCHOOL PRINCIPAL LEADERSHIP MODEL BASED ON INTEGRATED PATRIMONIAL MANAGEMENT, POLITICAL MANAGEMENT AND PROFESSIONAL MANAGEMENT - Zahraini; Rita Novita (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research focuses on the management of private school principals. The aim is to find the characteristics of the leadership model of private school principals based on integrated patrimonial management, political management and professional management at SDIT Nurul Fikri Aceh. This research uses a qualitative approach with data collection techniques namely documentation, observation and interviews. Research subjects are Foundation Chairmen, School Principals and Teachers. The research was conducted at the Nurul Fikri Aceh Integrated Islamic School. The research results show that: the characteristics of the leadership model for private school principals are based on integrated patrimonial management, political management and professional management at SDIT Nurul Fikri Aceh through the steps: (a) planning which includes formulating goals and preparing work programs; (b) organizing which includes forming a management team and job specifications; (c) implementation which includes the leadership of the school principal; (d) supervision which includes quality control and reporting.